EXPLORATION OF THE USE OF SCIENCE LEARNING MEDIA FOR BLIND STUDENTS AT SDLB NEGERI SEJAHTERA BOGOR CITY - Salsabila, Hasbiya; Suherman, Irman; Yektyastuti, Resti (Educational Researcher Journal, 2024)
Education is a basic need for everyone, including people with disabilities, who have the right to education. Children with visual impairments are usually called "blind children" in the field of special education. Based on data from the 2012 National Socio-Economic Survey, the number of Indonesian people with disabilities was 2.45%, according to the Central Statistics Agency (BPS), the number of children with special needs (ABK) in Indonesia reached 1.6 million children in 2017. According to Ministry of Education and Culture, West Java has a total of 688 blind students in 2021. The method used in this research is a literature review. Literature review is the first and important step in preparing a research plan. Literature review is a search and research of the literature by reading various books, journals and other publications related to the research topic, to produce an article regarding a particular topic or issue. In the initial stage of collecting articles based on the variables contained in the title, out of 10 articles, 4 articles were obtained that matched the title topic. At the article reduction stage, there were 4 articles that were not included because there were variables that did not match the title topic.